Utilization of Potato Wastewater for Chlorella Vulgaris Cultivation on Mars - Agnieszka Sidorowicz; Eliška Robenhauptová; Giacomo Fais; Mattia Casula; Bartolomeo Cosenza; Giovanni Antonio Lutzu; Giacomo Cao; Alessandro Concas (Chemical Engineering Transactions, 2025)
Potatoes have been demonstrated to be a crop potentially cultivable on Mars to sustain long term manned missions in the next future. Moreover, it has been recently demonstrated that starch from potatoes could be used on Mars to obtain a building material from locally available resources. However, both cooking and extracting starch from potatoes can generate large volumes of wastewater that, beyond posing a pollution burden can determine a loss of organic resources on Mars. Indeed, on the red planet, each organic stream represents a precious resource to produce useful materials to aid the sustainment of an eventual Martian colony. The current study aims to contribute to understanding the feasibility of growing Chlorella vulgaris in potato starch wastewater. This can lead to the remediation of the wastewater, the production of photosynthetic oxygen and the contextual generation of valuable microalgal biomass that can also represent a source of food for astronauts. Additional investigations were carried out to evaluate the nutritional quality of the obtained C. vulgaris biomass.